2017
DOI: 10.1123/ijsnem.2016-0196
|View full text |Cite
|
Sign up to set email alerts
|

A Sodium Drink Enhances Fluid Retention During 3 Hours of Post-Exercise Recovery When Ingested With a Standard Meal

Abstract: The purpose of this study was to examine the efficacy of water and a 50 mmol/L NaCl solution on postexercise rehydration when a standard meal was consumed during rehydration. Eight healthy participants took part in two experimental trials during which they lost 1.5 ± 0.4% of initial body mass via intermittent exercise in the heat. Participants then rehydrated over a 60-min period with water or a 50 mmol/L NaCl solution in a volume equivalent to 150% of their body mass loss during exercise. In addition, a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Findings from studies that have allowed participants to eat as part of the experimental protocol generally suggest that co-ingesting food and fluid improves rehydration, such that the magnitude of difference between beverages with different nutrient profiles (i.e. in terms of their potential to rehydrate) is attenuated (Maughan et al 1996;Brouns et al 1998;Ray et al 1998;Jones et al 2010;Pryor et al 2015;Campagnolo et al 2017;Evans et al 2017). Still, most studies have prescribed a small number of food items that may not reflect the participants' usual dietary behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from studies that have allowed participants to eat as part of the experimental protocol generally suggest that co-ingesting food and fluid improves rehydration, such that the magnitude of difference between beverages with different nutrient profiles (i.e. in terms of their potential to rehydrate) is attenuated (Maughan et al 1996;Brouns et al 1998;Ray et al 1998;Jones et al 2010;Pryor et al 2015;Campagnolo et al 2017;Evans et al 2017). Still, most studies have prescribed a small number of food items that may not reflect the participants' usual dietary behavior.…”
Section: Introductionmentioning
confidence: 99%
“…>1.25 L⋅ kg BM lost -1 ); and second, that the co-ingested food enhanced fluid retention -indeed, findings from previous studies that have allowed participants to eat as part of the experiment generally suggest that co-ingesting food and fluid increases retention of "simple" rehydration beverages (i.e. by delaying gastric emptying and attenuating osmotic diuresis) [13][14][15].…”
Section: Discussionmentioning
confidence: 95%
“…fluid volume and rate) and deny participants access to food. Studies that have allowed participants to eat during experiments generally indicate that the co-ingestion of food and fluid increases retention of "simple" rehydration beverages [13][14][15]. Still, most of these investigations have prescribed a small number of food items which may not reflect participants' usual dietary behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely that an athlete would not eat in the 4 h post-exercise period, and usually, this food intake would contain a mixture of macronutrients that might influence rehydration. A previous study [ 23 ] demonstrated that the addition of sodium to a rehydration solution still enhanced post-exercise rehydration, even when a standardised meal was consumed during the rehydration period. However, sodium and protein/macronutrients likely act via separate mechanisms to influence rehydration, and future studies should aim to examine the impact of eating typical recovery meals alongside various rehydration strategies to determine their combined success.…”
Section: Discussionmentioning
confidence: 99%
“…WP contained a small amount of sodium. Sodium is well known to enhance post-exercise rehydration [ 17 , 18 , 23 ], but sodium concentrations less than ~25–30 mmol/L do not significantly alter post-exercise rehydration. Therefore, the small amount of sodium consumed in the WP trial, which amounted to <6 mmol/L is unlikely to have influenced the rehydration responses in this study.…”
Section: Discussionmentioning
confidence: 99%